Beyond the Ridge: Exploring Fingerprints to Determine the Predominant Pattern in the Pakistani Population: Beyond the Ridge: Fingerprints to Determine the Predominant Pattern - Ashraf, Roman; Zafar, Durdana; Shabbir, Sheeba; Manzoor, Saima; Buzdar, Zulfiqar Ali; Tahir, Tayyaba (Pakistan Journal of Health Sciences, 2025)
Fingerprint patterns are widely used in forensic science due to their uniqueness and permanence. While pattern types like loops, whorls, and arches are well studied, fingerprint symmetry and its association with genetic and demographic factors remain underexplored in the Pakistani population. Objectives: To assess the distribution of fingerprint patterns and evaluate their symmetry by gender, age, ethnicity, region, hand dominance, and parental consanguinity. Methods: A cross-sectional study was conducted at Sahara Medical College, Narowal, from June to November 2021. Fingerprints from 110 participants were collected using the rolled ink method and categorized using the Henry Classification System. Fingerprint symmetry was evaluated by comparing matching fingers on both hands. Chi-square tests and Cramér’s V were used to analyzed associations. Results: Loops were the most frequent pattern, followed by whorls and arches. Symmetry was present in 45.5% of participants, while 54.5% were asymmetrical. Symmetry was significantly associated with gender (p=0.037), dominant hand (p=0.001), consanguinity (p<0.001), age group (p=0.003), region (p<0.001), and ethnicity (p<0.001). No significant link was found between symmetry and pattern type. Conclusions: It was concluded that fingerprint symmetry is influenced by several demographic and genetic factors. These findings support the need for population-specific biometric research and may contribute to forensic, genetic, and anthropological applications.